PENGARUH PENGGUNAAN SILICA FUME DAN SIKAMENT-NN PADA CAMPURAN BETON MUTU TINGGI MENGACU PADA METODE AMERICAN CONCRETE INSTITUTE (ACI) - Amran, Yusuf (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2014)
This research using a sample of test cylinder diameter of 15 cm and a height of 30 cm. Testing performed at 28 days of age and every age consists of 3 test objects. so it takes 3 test objects for each addition of silica fume content variations and sikament-nn. With the addition of silica fume 4 variations of 5%, 10%, 15%, and 20% as well as sikament-nn 0.5%, 1%, 1.5%, and 2%, had a total of 27 test objects.